Apakah Komisaris Independen Memiliki Peran Moderasi Dalam Hubungan Manajemen Laba Dan Nilai Perusahaan? - Amrie Firmansyah; Dita Ardhya Ramadini; Rizal Nur Arif; I Gede Dupopadana (Journal of Financial and Tax, 2023)
Shareholders commonly use earnings information to evaluate the company's operating success. Also, earnings data can be used in fundamental analysis while making investment decisions in the capital market. Earnings data, however, are not always reported under actual conditions. This research aims to look into the impact of earnings management on firm value. In addition, an independent commissioner serves as a moderating variable in this study. Purposive sampling was employed to collect 135 observations from 45 infrastructure sector companies listed on the Indonesia Stock Exchange between 2019 and 2021. Multiple linear regression was used to analyze hypothesis testing for panel data. According to the findings of this study, earnings management does not affect business value. Furthermore, independent commissioners do not affect the detrimental impact of earnings management on firm value.